2020
DOI: 10.3390/agriculture10030084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drip Irrigation with Plastic on Photosynthetic Characteristics and Biomass Distribution of Muskmelon

Abstract: An experiment was conducted in China to develop guidelines for the mulching drip irrigation of commercial muskmelon crops. Three sets of factors were laid out in rows to give a three × three factorial design. First, plastic covers were placed over the entire growing area (rows and inter-rows, or full), over the rows (half), or no plastic applied (none). Second, there was one irrigation pipe per row (T1), three pipes for four rows (T3/4), or one pipe for two rows (T1/2). Finally, the plants were irrigated when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Higher shallow soil moisture tends to increase soil water-filled porosity and reduce soil aeration, making the total dry matter accumulation of C1 is slightly lower than C2 by about 0.86% [8]. Wang et al [46] study found that Pn and Gs of muskmelon leaves increased at first and then decreased with the increase of capillary arrangement density, which was inconsistent with the conclusion that Pn and Gs of tomato leaves increased with the increase of capillary arrangement density. It may be due to the fact that the difference of irrigation control methods, Wang et al adopt the percentage control of field water holding rate, so it is difficult to ensure that the irrigation quantity of different capillary arrangement density is the same.…”
Section: Effects Of Capillary Arrangement Density On Photosyntheticmentioning
confidence: 88%
See 1 more Smart Citation
“…Higher shallow soil moisture tends to increase soil water-filled porosity and reduce soil aeration, making the total dry matter accumulation of C1 is slightly lower than C2 by about 0.86% [8]. Wang et al [46] study found that Pn and Gs of muskmelon leaves increased at first and then decreased with the increase of capillary arrangement density, which was inconsistent with the conclusion that Pn and Gs of tomato leaves increased with the increase of capillary arrangement density. It may be due to the fact that the difference of irrigation control methods, Wang et al adopt the percentage control of field water holding rate, so it is difficult to ensure that the irrigation quantity of different capillary arrangement density is the same.…”
Section: Effects Of Capillary Arrangement Density On Photosyntheticmentioning
confidence: 88%
“…After washing, the stems, leaves, fruits, and roots were dried in an oven at 105°C for 15 min, followed by drying at 75°C to constant weight. Finally, the dry matter mass was obtained [46].…”
Section: Dry Matter Accumulationmentioning
confidence: 99%
“…The use of covers is one of the most efficient organic weed control techniques, based upon the use of the crop residue of wheat, corn, rice, as well as polyethylene, biodegradable plastic, among others [4][5][6][7][8]. This technique has mainly been studied in vegetables [9][10][11][12][13][14][15], cereals [13,[15][16][17][18][19], some fruit species [1,4,8,20,21] and in forestry [6]. Several studies have demonstrated effects on weed control [18], fruit yield [6,[13][14][15]18], fruit weight, plant development [1], the absorption and accumulation of nutrients in plants [4,10,11], water use efficiency [4,11,[15][16][17]22], changes in soil temperatures [16,17] and cover effects on root growth [23].…”
Section: Introductionmentioning
confidence: 99%
“…This technique has mainly been studied in vegetables [9][10][11][12][13][14][15], cereals [13,[15][16][17][18][19], some fruit species [1,4,8,20,21] and in forestry [6]. Several studies have demonstrated effects on weed control [18], fruit yield [6,[13][14][15]18], fruit weight, plant development [1], the absorption and accumulation of nutrients in plants [4,10,11], water use efficiency [4,11,[15][16][17]22], changes in soil temperatures [16,17] and cover effects on root growth [23]. However, it is also necessary to evaluate fruit quality (firmness and size) and physiological characteristics to minimize stress in the plant, influenced by the use of mulches.…”
Section: Introductionmentioning
confidence: 99%